Geriatric giants among the elderly - Adrian Bartoszek; Barbara Niedorys; Kamil Szalast (Kazimierz Wielki University, 2019)
Geriatric giants are chronic, multisamplant, progressive disorders that lead to functional disability and deteriorate the quality of life of older people. The risk of their occurrence increases with age. They do not pose a direct threat to life, but are difficult to treat, reduce social contacts and increase the dependence of older people on carers. We include among them mobility disorders and falls, visual and auditory disturbances, depression and dementia, incontinence and stool incontinence. These diseases interact with each other. One disease contributes to the occurrence of the next, while those that appear strengthen the one that was diagnosed earlier. They are an element of the so-called cycles and geriatric cascades. GG (geriatric giants) is a significant medical problem. Patients or their carers do not report this to the medical staff, considering that they are a natural consequence of aging or that their treatment is impossible. The aim of the work is to present geriatric giants occurring among older people and to identify screening tools used to assess the risk of individual geriatric problems.